greet guys, (hyperbolic not trigonometry)

since sinh-1 (x) = ln(x + surd(x^2 +1) )

cosh-1 (x) = ln(x + surd(x^2 -1) )

therefore, prove that sinh-1 (x) = (cosh-1(surd(x^2 +1))

anyone please..

Printable View

- January 14th 2010, 04:33 PMvocybera kind of trigonometry proving.
greet guys, (hyperbolic not trigonometry)

since sinh-1 (x) = ln(x + surd(x^2 +1) )

cosh-1 (x) = ln(x + surd(x^2 -1) )

therefore, prove that sinh-1 (x) = (cosh-1(surd(x^2 +1))

anyone please.. - January 14th 2010, 06:38 PMJhevon